RESILIENCE ASSESSMENTS IN SOCIAL WORK: THE CASE OF THE SA DEPARTMENT OF DEFENCE - van Breda, Adrian D (Social Work/Maatskaplike Werk, 2011)
In recent years there has been a growing interest in social work literature in the strengths (Saleebey, 2008) and assets (Kretzmann & McKnight, 1993) of people and systems. This interest has involved a shift away from the dominant preoccupation with pathology and deficits that has characterised much of the history of social work (Bendor, Davidson & Skolnik, 1997; Weick & Saleebey, 1995). Part of the appeal of the strengths perspective is its alignment with the social values of human dignity and respect for client self-determination (Healy, 2005). While the strengths and resilience perspectives have become well established in social work, there is relatively little literature on the processes of assessment from these perspectives. In many ways the resilience and strengths perspectives are just that – perspectives, ways of looking at the world, a political stance that we as practitioners take towards our client systems. This is appropriate as it points towards the value base of social work; but these perspectives must also be translated into clear practice guidelines.